THE IMPACT OF COVID-19 ON THE DEVELOPMENT AND COURSE OF AUTOIMMUNE DISEASES: A LITERATURE REVIEW - Karol Poplicha; Piotr Sobkiewicz; Aleksandra Piech; Konrad Poplicha; Patrycja Ucieklak; Martyna Grodzińska; Maria Ufniarska; Tomasz Ufniarski; Justyna Moszkowicz; Karolina Pasierb; Patrycja Kardasz; Bartłomiej Siuzdak; et al. (International Journal of Innovative Technologies in Social Science, 2025)
Background: There is growing evidence to support an association between the SARS-CoV-2 infection and the onset or flare of ADs (autoimmune diseases) in pediatric and adult patients. Immunological factors in these processes include molecular mimicry, hyperactivation of the immune system, and others. Moreover, a new clinical entity (Multisystem Inflammatory Syndrome in Children (MIS-C)) is an example of a severe immunologic mediated pattern after COVID-19.Objective: This review describes available evidence regarding the impact of COVID-19 infection on the occurrence and course of autoimmune diseases in children as well as in adults. Significant emphasis is placed on population studies regarding the diagnosis of autoimmune diseases and their natural history, the immunological mechanisms, and the impact of COVID-19 vaccination in the setting of autoimmunity.Methods: This review was conducted using findings of scientific search databases PubMed, Google Scholar and Scopus with words: COVID-19, SARS-CoV-2, autoimmunity, autoimmune diseases, rheumatic diseases, COVID-19 vaccination, MIS-C, molecular mimicry. Articles were selected based on relevance, methodological quality, and adherence to PRISMA 2020 guidelines.Results: The immune dysregulation of SARS-CoV-2 infection might induce the onset of autoimmune diseases. Increased rates of newly diagnosed autoimmune diseases, such as type 1 diabetes, systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA), have been reported in both adult and pediatric populations following COVID-19. While autoimmune phenomena may rarely occur with COVID-19 vaccines, the risk is much higher with natural infection.Conclusion: Further studies and systematic immunological follow-up of patients after COVID-19 are essential for the early detection and effective management of autoimmune complication.